Pinus resinosa Tree-Ring Latewood Response to Daily-Scale Precipitation Variability at Lake Itasca, Minnesota - Trumper, Matthew L.; Griffin, Daniel; Montpellier, Evan E.; Kipfmueller, Kurt F. (Frontiers in Water, 2022)
Analysis of daily scale climate observations alongside sub-annual tree-ring data offers new potential for contextualizing climate change in the Great Lakes region. This pilot study combined daily observations from a high-quality station record with a co-located chronology of Pinus resinosa latewood width at Lake Itasca, Minnesota. Analytically robust approaches were used to evaluate trends in observational data and to compare day-wise aggregated climate observations with tree rings over the eleven-decade common period. The Itasca record exhibited significant increases in warm-season precipitation, minimum temperature in all seasons, and lengthening of the freeze-free season. Correlation analyses verified a strong, multi-month warm-season precipitation response in Pinus resinosa latewood width. Distinct from previous work, daily data analyses were used to fingerprint an approximately two-week period starting in late July when rainfall variability was historically a major control on interannual tree growth. Climatologically, the timing of this subseasonal critical climate period corresponds with a relative minimum in mean midsummer precipitation. Since the 1980s, the latewood correlation with midsummer rainfall has vanished, and the seasonal-scale rainfall response diminished considerably. This result, new for Pinus resinosa in Minnesota, is consistent with studies showing a declining relationship between tree growth and drought in the Midwest United States. Further attribution analyses emphasizing daily-scale phenomena are needed to elucidate mechanisms responsible for the tree-growth response to variability, change, and extremes in climate throughout the Great Lakes region, where the biophysical and socioeconomic impacts of climate change are multifaceted issues of increasing urgency.